Asymmetric Dearomatization of 1‐Aminonaphthalene Derivatives through C–C Bond Formation with Electron‐Rich Heterocycles as Nucleophiles. Issue 20 (5th June 2015) - Baba, Takafumi; Oka, Junko; Noguchi, Keiichi; Tanaka, Ken
Abstract: A cationic gold(I)/axially chiral biaryl bis(phosphine) complex has been employed to catalyze the asymmetric dearomatization reactions of 1‐aminonaphthalene derivatives through a C–C bond‐forming reaction with electron‐rich heterocycles as the nucleophiles. These reactions afford pentacyclic heterocycles in good yields with moderate enantiomeric excess ( ee ) values. Abstract : A cationic gold(I)/axially chiral biaryl bis(phosphine) complex has been employed to catalyze the asymmetric dearomatization of 1‐aminonaphthalene derivatives through a C–C bond‐forming reaction with electron‐rich heterocycles as the nucleophiles. These reactions afford pentacyclic heterocycles in good yields with moderate enantiomeric excess ( ee ) values.